Perancangan Aplikasi Ticketing Helpdesk Berbasis Web Untuk Meningkatkan Layanan Divisi Sapras Universitas Tangerang Raya Menggunakan Metode Waterfall - Ikhsan Maulana Ibrahim (Journal Information Technology Engineering and Science (JITES), 2026)
The management of facility damage complaints at Universitas Tangerang Raya previously ran conventionally using logbooks and WhatsApp, causing data accumulation, lost files, and slow response times. This study aims to design a web-based Ticketing Helpdesk application as a single point of contact for campus infrastructure reporting. The system development methodology used is Waterfall, which includes requirements analysis, design, coding based on the Laravel framework and MySQL database, and functional testing using Black Box Testing. The efficiency analysis results indicate that the implementation of the new system significantly cuts complaint handling time from an average of 3 days (72 hours) to only 8 hours, equivalent to an 88.89% efficiency increase. User Acceptance Testing (UAT) results using a dichotomy scale questionnaire administered to the Sarpras Division staff also showed an absolute feasibility rate of 100%. In conclusion, the helpdesk ticketing application on the https://helpdesk.untara.ac.id domain successfully automates manual bureaucracy into a transparent, accountable, and stable digital administration system to support academic service quality.